Reducing onchocerciasis-associated morbidity in onchocerciasis-endemic foci with high ongoing transmission: a focus on the children - Colebunders,R; Kaiser,C; Basanez,M-G; Olliaro,P; Lakwo,T; Fodjo,JNS (International Journal of Infectious Diseases, 2022)
Efforts are being directed toward the elimination of onchocerciasis transmission in endemic areas with community-directed treatment with ivermectin (CDTI) in Africa, which greatly reduces onchocerciasis-associated disease. However, onchocerciasis remains a major public health problem in areas of South Sudan, the Democratic Republic of the Congo, Cameroon, and the Central African Republic. Strengthening onchocerciasis elimination efforts in areas with a high prevalence of disease burden is crucial to decrease transmission, morbidity, and mortality. We argue that clinical trials are needed to investigate the safety and efficacy of ivermectin treatment of Onchocerca volvulus-infected pregnant women and children younger than 5 years. Crucially, 6-monthly administration of ivermectin in school-age children at risk of onchocerciasis-associated epilepsy could be achieved by supplementing annual CDTI with an extra round of ivermectin treatment during Child Health Days in schools and/or other distribution sites every year. These strategies would help achieve the elimination of onchocerciasis and its associated disease burden.